APLIKASI LAPORAN PENJUALAN PAKAIAN BERBASIS WEB (STUDI KASUS: TOKO ALIA FASHION BOUTIQUE TEMBILAHAN) - Ayu Wida Ningsih; Fitri Yunita (Indragiri Islamic University, 2023)
Until now, the Alia Fashion Boutique Tembilahan store does not yet have a data storage application that can help speed up the data entry process and speed up checking store information. The purpose of the benefits of this research can help administrative work in the form of providing a web-based clothing sales report application as a tool in managing sales data. The application that was built was made using the PHP programming language with the Codeigneter Framework, using MySQL as a database, the Waterfall method as a software development method, the analysis used in PIECES research, the design used by UML, the testing used by Black Box with Functionality and Usability Instruments. With this web-based clothing sales report application, it is hoped that it can help performance and make it easier to find store information for admins and cashiers.